High latitude local scale temperature complexity: the example of Kevo Valley, Finnish Lapland. (15th August 2012) - Pike, G.; Pepin, N. C.; Schaefer, M.
Abstract Subarctic Scandinavia is expected to experience significant temperature increases over the next century. How this increase will influence local scale climate is largely unknown. This study examines local scale temperature variability in the subarctic where the unusual solar geometry means that the classic diurnal cycle of mid‐latitudes has limited application. Near surface air temperature data were collected from a high density network of 60 temperature data loggers covering approximately 20 km2 in the valley system around Kevo Subarctic Research Station (69°45′N, 27°1′E). Temperature data was collected at 30 min intervals from September 2007 to March 2010, along with additional temperature and cloud cover data from the Kevo station. NCEP/NCAR reanalysis data was used to reconstruct synoptic conditions for the area at 6‐h intervals. Lapse rates and regression of surface temperatures on free air temperatures are used to investigate local temperature variability. Median absolute yearly deviation analysis of the site temperatures was used to assess the representativeness of Kevo Station. The results show intense (up to + 80 °C km−1) and persistent inversion events during the winter months (NDJ) which are broken up by mechanical effects. In the transition from winter into spring (FMA) these inversions still occur but increasing radiation imposes a diurnal pattern on their formation and destruction. As snow cover peaks in spring the interaction between surface albedo, land cover and radiation serves to amplify the diurnal cycle in lapse rates. Summer lapse rates are modified by the presence of open water at low elevations. These results suggest that expected land cover and synoptic changes due to regional warming will act to decrease the frequency and intensity of inversion formation, steepening mean lapse rates and therefore increasing the relative amount of warming in valley floor locations. Copyright © 2012 Royal Meteorological Society